An integrated dynamic power safeguard system using defence surveillance robots. (2016) - Mathankumar, M.; Preethi, M.; Ranjani, R. Kala; Sugandhi, N.
The defence environment is prone to many security threats. Human surveillance will put the human life into stake. Hence, this system developed with a robotic vehicle for restricting the unauthorised persons intruding the defence area. For identifying the authorised persons the passive infrared (PIR) sensor and radio frequency identification (RFID) system is deployed. Initially, the sensor identifies whether the entering object is human or not, then the RFID reader checks for the identification of that person. The robotic vehicle consists of a webcam for capturing the image of the unauthorised persons. If any unauthorised person enters the restricted area, the webcam sends the information to control section wirelessly. This paper mainly focuses on the robot which has the significant twofold batteries one for the normal use of robot movements, the other one consumes the energy constantly from the solar source or through RF waves.